The Economics of Education and Training 2008
DOI: 10.1007/978-3-7908-2022-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Employment effects of the provision of specific professional skills and techniques in Germany

Abstract: Auch mit seiner neuen Reihe "IAB-Discussion Paper" will das Forschungsinstitut der Bundesagentur für Arbeit den Dialog mit der externen Wissenschaft intensivieren. Durch die rasche Verbreitung von Forschungsergebnissen über das Internet soll noch vor Drucklegung Kritik angeregt und Qualität gesichert werden.Also with its new series "IAB Discussion Paper" the research institute of the German Federal Employment Agency wants to intensify dialogue with external science. By the rapid spreading of research results v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 23 publications
5
34
1
Order By: Relevance
“…Because of the short time horizon available to observe outcomes, the negative lock‐in effects drive their results. Fitzenberger and Speckesser (2005) and Speckesser (2004) draw their sample from the same administrative records, as we do. However, they restrict their analysis to one special type of government‐sponsored training and observe outcomes for 36 months after the beginning of the programme only, compared with 96 months in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the short time horizon available to observe outcomes, the negative lock‐in effects drive their results. Fitzenberger and Speckesser (2005) and Speckesser (2004) draw their sample from the same administrative records, as we do. However, they restrict their analysis to one special type of government‐sponsored training and observe outcomes for 36 months after the beginning of the programme only, compared with 96 months in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Speckesser (2004), who focuses on training conducted in the period 1993–94, finds no significant effects thereafter, mainly because of rapidly decreasing sample size towards the end of his observation period. Fitzenberger and Speckesser (2005), who cover a longer period of programme participation (1990–97), obtain positive employment effects of about 5–10% points about 20 months after the programme start.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Schochet et al () for the USA, Larsson () for Sweden, Bergemann et al (), Lechner et al () and Fitzenberger and Völter () for East Germany, Jespersen et al () for Denmark, Fitzenberger and Speckesser () and Rinne et al () for Germany, and Card et al () for European countries showed a dynamic training effect with significant variation over time after the implementation of training programmes. Usually, the employment or earnings effects were nonsignificant, zero or negative initially, but then became positive in the medium to long run.…”
Section: Results From the Literature Analysismentioning
confidence: 93%
“…With respect to distance, 2 studies with regional variables demonstrated a significant relationship between distance to nearest market, industrial areas, county, town or city and training outcomes (especially for earnings and the probability of technology adoption) (Ning & Wu, ; Wu et al, ). For geographical divisions, positive effects were stronger in West Germany compared to East Germany (Fitzenberger & Speckesser, ; Rinne et al, ). There was also a disparity in unemployment rates between the German‐speaking cantons and the non‐German‐speaking cantons in a Swiss study (3.4% vs 7.1% in 1995) (Gerfin & Lechner, ).…”
Section: Results From the Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation